[A New View of the Economics of International Readjustment]: A Comment - Harrod, R. F. (Review of Economic Studies, 1946)
Journal Article A Comment Get access R. F. Harrod R. F. Harrod Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 14, Issue 2, 1946, Pages 95–97, https://doi.org/10.2307/2296089 Published: 01 September 1946